Dampak Pemanfaatan Gawai terhadap Pemerolehan Bahasa Anak Usia 3-6 Tahun: Pendekatan Ramah Anak - Romadhon, Sahrul; Mita Cintiya Sari; Mochamad Arifin Alatas (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This study aims to explore the impact of gadget use on language acquisition in children aged 3-6 years using a child-friendly approach. The use of gadgets is increasingly widespread among children, raising concerns about its effects on their language development. This study employs qualitative methods, including observation and interviews with children aged 3-6 years in the vicinity of Desa Lemper Rt 001/002 Pademawu, Pemekasan. The results indicate that children who excessively use gadgets tend to experience delays in vocabulary acquisition and verbal communication skills. However, with a child-friendly approach, such as the use of educational applications and proper parental supervision, negative impacts can be minimized. Children who use gadgets in a controlled manner with appropriate content show improvements in word recognition and storytelling abilities. In conclusion, gadgets do not always negatively impact children's language development if used wisely and properly supervised. It is crucial for parents and educators to understand how to positively and child-friendly utilize technology to support optimal language development. This research provides significant contributions in the effort to integrate technology into children's lives without neglecting the aspects of their language development.